2020
DOI: 10.11604/pamj.supp.2020.35.2.25095
|View full text |Cite
|
Sign up to set email alerts
|

Staff risks stratification in preparation for COVID-19 in a tertiary healthcare facility in Nigeria

Abstract: Introduction: this report is a documentation of a staff risk stratification programme, undertaken in University of Benin Teaching Hospital, with outcomes, and the actions taken to protect staff. Methods: an adapted risk stratification tool was circulated to all staff through their respective heads of departments/units. Staff were expected to voluntary assess their health and risk status in the context of COVID-19, using the tool. A central multi-disciplinary screening c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This 860-bed facility renders promotive, preventive, curative, and rehabilitative services in various departments, including internal medicine, surgery, pediatrics, mental health, community health, obstetrics and gynecology, radiology, ear, nose and throat, anesthesiology, ophthalmology, family medicine, and dentistry. 22,23 The UBTH currently has a staff strength of 4,220.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This 860-bed facility renders promotive, preventive, curative, and rehabilitative services in various departments, including internal medicine, surgery, pediatrics, mental health, community health, obstetrics and gynecology, radiology, ear, nose and throat, anesthesiology, ophthalmology, family medicine, and dentistry. 22,23 The UBTH currently has a staff strength of 4,220.…”
Section: Methodsmentioning
confidence: 99%
“…A risk stratification tool was adapted to identify vulnerable staff who were re-deployed to nonclinical areas or asked to work from home. 23 In addition to increasing the purchase and availability of face masks, gloves, and eye goggles (necessary for standard precautions and transmission based precautions), relevant hospital departments embarked on the local production of plastic aprons, coveralls, and face shields. Also, information education and communication posters on COVID-19 were placed at strategic locations, and advisories were regularly communicated to staff.…”
Section: Methodsmentioning
confidence: 99%
“…A study on staff risk stratification in UBTH found that core clinical staff such as doctors and nurses made up over 75% of workers in the high-risk category [ 29 ]. In the present study however, pharmacists had the highest odds of having high risk perception (OR: 5.4; 95% CI = 1.776-6.450).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure adherence to recommended IPC measures, individual health facilities are required to conduct COVID-19 risk assessment across all the departments to rank the risks of exposure [ 17 ]. Ranking of risks will help to identify high-risk departments, such as the emergency department, to inform on the need to scale up the provision of IPC equipment and materials in such departments.…”
Section: Strategies For Ensuring Adequate Preparedness and Response During The Third Wave Of The Covid-19 Pandemic On The African Continementioning
confidence: 99%